2004
DOI: 10.1002/mrm.20149
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tumor blood perfusion by high‐resolution dynamic contrast‐enhanced MRI: A preclinical study of human melanoma xenografts

Abstract: A noninvasive method to obtain high-resolution images of tumor blood perfusion is needed for individualized cancer treatments. In this study we investigated the potential usefulness of dynamic contrast-enhanced MRI (DCE-MRI), using human melanoma xenografts as models of human cancer. Gadopentetate dimeglumine (Gd-DTPA) was used as the contrast agent, and DCE-MRI was performed at a voxel size of 0.5 ؋ 0.2 ؋ 2.0 mm 3 with spoiled gradient-recalled sequences. We obtained images of E ⅐ F (where E is the extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
118
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 34 publications
7
118
0
Order By: Relevance
“…Second, the DCE-MRI data were analyzed with the use of a mean arterial input function rather than individual arterial input functions, and thus any variation in the injection rate among mice was ignored. However, the mean arterial input function was established by analyzing 24 blood samples from 12 mice, and the data points suggested that the arterial input function did not differ significantly among mice (15). Furthermore, complete arterial input functions have been determined for individual mice by DCE-MRI of the heart, and these curves did not differ significantly from each other or from the mean arterial input function (15).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, the DCE-MRI data were analyzed with the use of a mean arterial input function rather than individual arterial input functions, and thus any variation in the injection rate among mice was ignored. However, the mean arterial input function was established by analyzing 24 blood samples from 12 mice, and the data points suggested that the arterial input function did not differ significantly among mice (15). Furthermore, complete arterial input functions have been determined for individual mice by DCE-MRI of the heart, and these curves did not differ significantly from each other or from the mean arterial input function (15).…”
Section: Discussionmentioning
confidence: 99%
“…The DCE-MRI experiments and the subsequent image processing and analysis were carried out by using a procedure described in detail previously (15,18). Briefly, Gd-DTPA (Schering, Berlin, Germany) was administered intravenously in a bolus dose of 0.3 mmol/kg of body weight by using the protocol developed by Benjaminsen et al (15). The imaging was performed with a 1.5-T whole-body scanner (Signa, General Electric, Milwaukee, WI, USA) by using a 13-cm-long cylindrical slotted tube resonator transceiver mouse coil with a diameter of 40 mm.…”
Section: Dce-mrimentioning
confidence: 99%
See 3 more Smart Citations